2019
DOI: 10.1111/imm.13137
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Batf3‐deficient mice from experimental cerebral malaria correlates with impaired cytotoxic T‐cell responses and immune regulation

Abstract: Summary Excessive inflammatory immune responses during infections with Plasmodium parasites are responsible for severe complications such as cerebral malaria (CM) that can be studied experimentally in mice. Dendritic cells (DCs) activate cytotoxic CD8+ T‐cells and initiate immune responses against the parasites. Batf3−/− mice lack a DC subset, which efficiently induces strong CD8 T‐cell responses by cross‐presentation of exogenous antigens. Here we show that Batf3−/− mice infected with Plasmodium berghei ANKA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Another study also showed the high BATF3 expression in CRC [ 17 ]. More importantly, BATF3 has been suggested to reduce T cell activity and induce immune reaction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also showed the high BATF3 expression in CRC [ 17 ]. More importantly, BATF3 has been suggested to reduce T cell activity and induce immune reaction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…injection of 10 mg/kg xylazin (Rompun R Bayer, Germany) + 100 mg/ml ketamine (Ratiopharm GmbH Germany). Mice were intracardially perfused with 1x PBS for 5 min to remove circulating and non-adhered blood leukocytes from the organs (12).…”
Section: Isolation Of Stromal Vascular Fraction From Adipose Tissue Amentioning
confidence: 99%
“…Protecting the host brain vascular system and neurons and modulating the host inflammatory response to infection might be effective strategies to improve the success of antimalarial therapy for CM . Dysfunction of the brain blood vessels might be the primary cause of CM, preventing the re-establishment of brain homeostasis and leading to treatment failure. , …”
mentioning
confidence: 99%
“…4 Dysfunction of the brain blood vessels might be the primary cause of CM, preventing the re-establishment of brain homeostasis and leading to treatment failure. 5,6 Tetramethylpyrazine (TMP) is the primary active alkaloid component of the traditional Chinese medicine Chuanxiong. 7,8 TMP has been demonstrated to increase cerebral blood flow, improve microcirculation, inhibit the production of proinflammatory factors, and protect learning and memory functions.…”
mentioning
confidence: 99%